Childhood maltreatment and suicide attempts in prisoners: a systematic meta-analytic review. Issue 1 (30th October 2019) - Angelakis, Ioannis; Austin, Jennifer L.; Gooding, Patricia
Abstract: In the past decade, the links between core types of childhood maltreatment and suicidal acts have become an increasingly important area of investigation. However, no meta-analytic review has examined this relationship in prisoners. We undertook the first systematic meta-analytic review examining the link between childhood maltreatment and suicide attempts in prisoners to redress this important gap. We searched Medline, PsychINFO, Embase, Web of Science and CINAHL from inception until August 2019. Meta-analyses using random effect models were applied, and heterogeneity was quantified using the I 2 statistic. Publication bias and risk of bias across studies were assessed. We identified 24 studies comprising 16 586 prisoners. The rates of different types of childhood maltreatment ranged between 29% and 68% [95% confidence interval (CI) 18–81%]. The rate of suicide attempts in prisoners was 23% (95% CI 18–27%). Main results demonstrated that sexual abuse [odds ratio (OR) 2.68, 95% CI 1.86–3.86], physical abuse (OR 2.16, 95% CI 1.60–2.91), emotional abuse (OR 2.70, 95% CI 1.92–3.79), emotional neglect (OR 2.29, 95% CI 1.69–3.10), physical neglect (OR 1.57, 95% CI 1.27–1.94) and combined abuse (OR 3.09, 95% CI 2.14–4.45) were strongly associated with suicide attempts in prisoners. There was an indication of publication bias. Duval and Tweedie's trim-and-fill method was applied, which increased the odds for suicide attempts. Given the high rates of prison suicide deaths and suicide attempts, our findings suggest an urgent need for targeted suicide prevention priorities for prisoners, with a particular focus on ameliorating the effects of childhood traumatic experiences on suicidal prisoners.